Treatment of general paralysis by the method of Von Wagner Jauregg - Pardo Figueroa, Pedro (1925)
Many are complex síndromesd offering cerebrospinal syphilis. And, on the other hand, so like the table for consideration by the clinician presented the various etiological factors - more than syphilis - are originators transient or permanent disorders in the complicated structure of the central nervous system, the demarcation of the elements of tables is as varied task more difficult, delicate, and it is mainly because of the importance of having accurate classification for prognosis and for treatment's prosecutions, the likely explanation especially here in the case at hand, is as great or greater importance than in other disease entities.